Hydrogen production by Co-based bimetallic nano-catalysts and their performance in methane steam reforming. (18th March 2020) - Shen, Qiuwan; Jiang, Yuhang; Xia, Feihong; Wang, Biao; Lv, Xinrong; Ye, Weiqiang; Yang, Guogang
Abstract: Methane steam reforming (MSR) reaction is a promising industrial hydrogen production technology. In this study, the impregnation method was deployed to prepare mono Co and Co-based bimetallic catalysts loaded on CeO2 nanoparticles as the catalysts for MSR. Results show that the improved Co-based bimetallic catalysts have good performance compared to the mono one. The best catalyst sample was Co-Ni/CeO2 which resulted in the CH4 conversion of 76.1%, H2 selectivity of 58.5% and H2 yield of 44.5%. Furthermore, the H2 selectivity increased significantly from 58.5% to 77.2% with the increase of the total Co-Ni metal loading amount.